Business Design Model Canvas Tourism Cempaka Banjarbaru City - Firdaus, Firdaus; Mardah, Siti (Jurnal Ekonomi, 2024)
In business design, the Business Model Canvas (BMC) is an invaluable tool in identifying opportunities, developing strategies, and understanding the key components that form the foundation of a business. For tourism businesses, BMC provides a clear view on how to detail and design an effective business model. It includes key components such as customer segments, value proposition, distribution channels, customer relationships, revenue sources, key resources, key activities, key partners, and cost structure. BMC enables travel businesses to focus on proper customer segmentation, offer appropriate value propositions, manage efficient distribution channels and build strong customer relationships. Additionally, it also helps in identifying diverse revenue sources and key resources required to support business operations. Key activities and key partners contribute to the provision of exceptional tourism experiences. All this must be managed efficiently within the framework of an adequate cost structure. BMC design is a key step in planning a sustainable and successful tourism business. This helps in responding better to market changes, trends and business challenges. By focusing on BMC elements, tourism businesses can continue to innovate and adapt to changes in the dynamic business environment.